2011
DOI: 10.1038/npp.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phenylalanine/Tyrosine Depletion Reduces Motivation to Smoke Cigarettes Across Stages of Addiction

Abstract: The neurobiology of tobacco use is poorly understood, possibly in part because the relevant mechanisms might differ depending on past nicotine exposure and degree of addiction. In the present study we investigated whether these factors might affect the role of dopamine (DA). Using the acute phenylalanine/tyrosine depletion method (APTD), DA synthesis was transiently decreased in three groups of abstinent smokers (n=47): (1) early low-frequency smokers, who had smoked a maximum of five cigarettes per day for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 58 publications
1
54
1
1
Order By: Relevance
“…49,50 The present study indicates that lowered DA can also reduce the motivation to work for a nonpharmacological reward. The measure of motivation was the PR breakpoint task.…”
Section: Discussionmentioning
confidence: 94%
“…49,50 The present study indicates that lowered DA can also reduce the motivation to work for a nonpharmacological reward. The measure of motivation was the PR breakpoint task.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, subtler augmentations of DA, such as L-3,4-dihydroxyphenylalanine (L-DOPA) administration, show no effect on hedonic response, despite clear modulation of motivation and response vigor (Beierholm et al, 2013;Liggins et al, 2012;Sharot et al, 2012;Sharot et al, 2009). Further, transient reduction of DA increased subjective reports of boredom and apathy, with no effect on affective ratings (McLean et al, 2004;Venugopalan et al, 2011).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 98%
“…Also in keeping with animal studies, effort expenditure for rewards can be increased or decreased through either potentiation (Wardle et al, 2011) or attenuation (Venugopalan et al, 2011) of DA levels, and individual differences in striatal DA release predict effort-related preferences (Treadway et al, 2012b).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 99%
“…Administration of haloperidol and risperidone to normal human volunteers was shown to induce negative symptoms as measured by the Positive and Negative Symptoms Scale (Artaloytia et al, 2006). Furthermore, Venugopalan et al (2011) reported that catecholamine depletion reduced the tendency to work for cigarettes in smokers responding on a progressive ratio operant schedule.…”
Section: Pharmacological Induction Of Negative Symptomsmentioning
confidence: 98%